Design of InGaAsN/GaAs quantum well photodetector - Li, Wen. (2009)
Our human eyes can only see the visible part of the Electromagnetic Spectrum. Objects that do not emit and reflect visibly are invisible to human. However, with Quantum Well Infrared Photodetectors (QWIPs), objects that emit or reflect infrared radiation can be detected. QWIPs utilizing intersubband transitions have been widely investigated during the past years. In an n-type doped quantum well (QW), intersubband absorption is of interest because of its applications to far-infrared photodetectors. Based on this technology, NASA successfully fabricated 256X256 8-12 um GaAs/AlGaAs QWIP used for night vision camera. In this project, a simple InGaAsN/GaAs QWIP for 8-12 μm in conduction band is studied and designed by varying the composition of Indium (In) and Nitrogen (N), and quantum well width (WW). The effective mass program is used to calculate the InGaAsN QW conduction subbands and the absorption spectrum for different InGaAsN QW structures. With the help of computer simulation programs, the optimum design is achieved to meet both energy transition in two energy levels of 124meV as well as the strongest absorption among all appropriate results.